Persepsi Mahasiswa FISH UNIMA tentang Implementasi Materi Mata Kuliah dalam Pembentukan Karakter dan di Kehidupan Sosial - Mamonto, Fitri Herawati; Sufitriyono, Sufitriyono; Mesra, Romi (Jurnal Ilmiah Mandala Education (JIME), 2023)
The purpose of this study is to reveal students' perceptions regarding the learning materials provided by lecturers as educators whether they have a principle of usefulness in character building which is reflected in the attitudes and behavior of these students and so that these students are able to become part of social life that contributes positively and is beneficial to their environment. the. The research method used is a qualitative research method with observation and interview data collection methods. While the data analysis used from Miles Huberman is in the form of data collection, data reduction, data presentation and drawing conclusions. The results of this study are student perceptions about the implementation of course material in character building: increasing tolerance among students of different religions, internalizing the value of social care between students, not selecting and sorting friends on the basis of sara (ethnicity, religion, race, and intergroup), responsible for educational obligations. Student perceptions about the implementation of course material in social life: assisting students in adapting to the boarding house environment, helping students interact, and helping students overcome social problems